Protein Profiling of Orthosiphon Stamineus Embryogenic Callus Using a Proteomic Approach: Protein Profiles of Orthosiphon stamineus Embryogenic Callus - Dayangku Dalilah Mamat; Zaidah Rahmat; Tsun-Thai Chai; Fazilah Abd Manan (Journal of Tropical Life Science, 2022)
Orthosiphon stamineus is one of the most prominent medicinal herbs widely grown in Southeast Asia. Propagation of O. stamineus using tissue culture technique helps to rapidly produce samples for research purposes, increase the production of secondary metabolites and is considered as one of the strategies in plant genetic improvement. Despite vast information on O. stamineus pharmacological properties, the protein profile of this species is currently underexplored. In the present study, proteins expressed in embryogenic callus developed from O. stamineus leaves in Murashige and Skoog medium supplemented with 1-naphthaleneacetic acid (NAA) and 2,4-dichlorophenoxyacetic acid (2,4-D) were identified via Liquid chromatography- tandem mass spectrometry (LC-MS/MS). The presence of embryogenic callus was confirmed with microscope observation and Evan Blue assay. Using this proteomic approach, we identified peptides that represent 22 proteins localized to different cell compartments and involved in various biological and metabolic functions in plants. This finding is useful to improve our understanding of protein functions, thus their future applications could be further explored Â  Keywords: Callus, Embryogenic, Herb, Orthosiphon stamineus,Proteins